PENGARUH KETINGGIAN AIR TERHADAP PERTUMBUHAN DAN KELANGSUNGAN HIDUP BENIH IKAN KOI (CYPRINUS CARPIO): The Effect Of Water Depth On The Growth And Survival Of Koi Fish Seeds (Cyprinus carpio) - Kusnandi, Aan; Hamid, Hamid; Sumahiradewi, Luh Gede (Al-Aqlu: Jurnal Matematika, Teknik dan Sains, 2024)
Koi fish (Cyprinus carpio) is one of the most popular ornamental fish with high economic value and can compete in local and international markets. One of the obstacles in koi fish farming is growth and survival caused by changes in temperature. One of the factors that affect temperature changes is water level. This study aims to determine the effect of water level on the growth and survival of koi fish seeds. This study used an experimental method with a completely randomized design (CRD). There were 4 (four) treatments tested, namely P1 (15 cm) as control, P2 (20 cm), P3 (25 cm), and P4 (30 cm). Each treatment was repeated 3 times, resulting in 12 experimental units. The variables taken were fish length and weight, and water quality (temperature, pH, DO, ammonia). The results showed that. The ideal container water level and can provide the best results to support the growth of koi fish fry is 25 cm. At a water level of 25 cm, weight growth of 0.034 grams/day, length growth of 0.018 cm/day, specific growth rate of 0.021%/day, and survival rate reached 100%. Meanwhile, water quality parameters during the study were in the optimal range, namely temperature 19 - 23 °C, pH 7, dissolved oxygen 5 - 8 mg/L, and ammonia 00.1 - 0.06 mg/L.